PECULIARITIES OF EMPLOYING DISABLED PEOPLE IN ISRAEL - Galina Kozlovskaya; Natalia Borozinets (Вестник Северо-Кавказского федерального университета, 2022)
The article reveals comparative aspects of the organization of employment of persons with disabilities in Israel. The main focus of the authors is on public policy issues, legal aspects of ensuring access to education and further employment of students with disabilities and HIA. It also examines the experience of organizations that develop and implement programs for social support and job creation for people with disabilities.